PEDAGOGICAL POSSIBILITIES OF MORAL EDUCATION OF CHILDREN THROUGH FAIRY TALE THERAPY IN PRESCHOOL EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examined information on creating pedagogical opportunities in moral education for preschool children through the means of fairy tale therapy, gaining interest in children's fiction and teaching them such concepts as analyzing fiction. In the process of preschool education, the necessary recommendations were given for the use of fairy tale therapy and its use in training.